(untitled) (Comprehensive Journal of Science, 2025)
This study aims to analyze the reasons that make physics one of the most difficult subjects for third-year secondary school female students in Libya. This stage of education represents a critical period in the students’ lives due to its direct impact on their future academic paths. The study employed a descriptive-analytical approach, and a questionnaire was developed and distributed to a sample of students from several secondary schools in Libya. The results indicated that the difficulty of abstract physics concepts, the inadequacy of teaching methods used in the classroom, the lack of practical applications, and academic anxiety were among the main factors contributing to students’ perception of physics as a difficult subject. The study recommends renewing teaching methods, increasing interactive activities, and providing psychological and academic support for the students.